Pengaruh Perceived Organizational Support terhadap Burnout pada Polisi Wanita Polrestabes Bandung - Muhammad Ilyas Yusuf; Lisa Widawati; Ayu Tuty Utami (Bandung Conference Series: Psychology Science, 2024)
Abstract. Female police officers are a type of human service worker who has a heavy workload. A problem that often arises in relation to female police facing increasingly high job demands in the workplace is burnout. Burnout is a psychological syndrome which is an individual's reaction to prolonged work pressure (Maslach & Leiter, 1997). One of the factors that can reduce burnout is perceived organizational support. According to Rhoades & Eisenberger (2002), perceived organizational support is employees' perception of how much the organization values their contributions and cares about their welfare. The aim of this research is to see how much influence perceived organizational support and its aspects have on burnout in 56 Bandung Police Women. The measuring instrument used in this research is the perceived organizational support (POS) scale developed by Eisenberger et al. (1986) and adapted by Fahrian Lubis (2022). In addition, the Maslach Burnout Inventory – Human Service Survey (MBI-HSS) was developed by Maslach, Schaufeli & Leiter (2001) and adapted by Susilo et. al., (2023). The research results show that there is a significant positive influence of perceived organizational support on burnout, namely with R Square = .097. The results of all aspects of perceived organizational support have a significant effect with R Square = .225. Abstrak. Polisi wanita merupakan jenis pekerja human service yang memiliki beban kerja yang berat. Persoalan yang sering muncul berkaitan dengan polisi wanita dalam menghadapi tuntutan pekerjaan yang semakin tinggi ditempat kerja adalah burnout. Burnout merupakan sindrom psikologis yang merupakan reaksi individu terhadap tekanan pekerjaan yang berkepanjangan (Maslach & Leiter, 1997). Satu diantara faktor yang dapat menurunkan burnout yakni perceived organizational support menurut Rhoades & Eisenberger (2002) mengatakan bahwa perceived organisational support adalah persepsi karyawan mengenai seberapa besar organisasi menghargai kontribusi mereka dan peduli terhadap kesejahteraan mereka. Tujuan dari penelitian ini adalah untuk melihat seberapa besar pengaruh perceived organizational support dan aspeknya terhadap burnout pada 56 Polisi Wanita Polrestabes Bandung. Alat ukur yang dipergunakan dalam penelitian ini yaitu skala perceived organizational support (POS) yang dikembangkan oleh Eisenberger et al. (1986) dan diadaptasi oleh Fahrian Lubis (2022). Selain itu, Maslach Burnout Inventory – Human Service Survey (MBI-HSS) yang dikembangkan oleh Maslach, Schaufeli & Leiter (2001) dan diadaptasi oleh Susilo et. al., (2023). Hasil penelitian menunjukkan adanya pengaruh positif secara signifikan perceived organizational support terhadap burnout yakni dengan R Square = .097. Hasil seluruh aspek perceived organizational support berpengaruh signifikan dengan R Square = .225.